2010
DOI: 10.1523/jneurosci.2208-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Survival of Motor Neuron (SMN) Protein in Motor Neuronal Progenitors Functions Cell Autonomously to Cause Spinal Muscular Atrophy in Model Mice Expressing the Human Centromeric (SMN2) Gene

Abstract: Spinal muscular atrophy (SMA) is a common (ϳ1:6400) autosomal recessive neuromuscular disorder caused by a paucity of the survival of motor neuron (SMN) protein. Although widely recognized to cause selective spinal motor neuron loss when deficient, the precise cellular site of action of the SMN protein in SMA remains unclear. In this study we sought to determine the consequences of selectively depleting SMN in the motor neurons of model mice. Depleting but not abolishing the protein in motor neuronal progenito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

21
151
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(172 citation statements)
references
References 54 publications
(75 reference statements)
21
151
0
Order By: Relevance
“…Importantly, similar NMJ defects have been reported in type I (the most severe type) SMA human fetuses (10). SMA MNs have also been shown to be hyperexcitable and loss of proprioceptive synapses on the somata, and proximal dendrites of SMA MNs (MN deafferentation) occurs no later than P4 (11)(12)(13). These findings indicate that both peripheral (NMJs) and central (sensory-motor) synapses are affected in SMA mice at early stage of disease.…”
supporting
confidence: 71%
See 1 more Smart Citation
“…Importantly, similar NMJ defects have been reported in type I (the most severe type) SMA human fetuses (10). SMA MNs have also been shown to be hyperexcitable and loss of proprioceptive synapses on the somata, and proximal dendrites of SMA MNs (MN deafferentation) occurs no later than P4 (11)(12)(13). These findings indicate that both peripheral (NMJs) and central (sensory-motor) synapses are affected in SMA mice at early stage of disease.…”
supporting
confidence: 71%
“…These findings indicate that both peripheral (NMJs) and central (sensory-motor) synapses are affected in SMA mice at early stage of disease. Although SMA is clinically manifested primarily in MNs, recent studies have shown that other cell types and nonneuronal tissues are also involved (13,14,15). SMN, as part of the SMN-Gemins complex (16), functions in the assembly of Sm protein cores on snRNAs (U1, U2, U4, U5, U11, U12, and U4atac), a key step in snRNP biogenesis (17-20).…”
mentioning
confidence: 99%
“…On the other hand, in several studies, including our own, selective depletion of SMN in motor neurons induces NMJ defects, and restoration of SMN rescues them, indicating a cell-autonomous mechanism (Park et al 2010;Gogliotti et al 2012;Lee et al 2012;Martinez et al 2012;Sahashi et al 2012Sahashi et al , 2013. This apparent discrepancy may be due to the extremely low SMN levels in motor neurons in these studies.…”
Section: Discussionmentioning
confidence: 56%
“…This unexpected finding indicates that the basal SMN protein levels in the CNS are already sufficient for normal mouse development, provided that a sufficient increase in SMN levels in peripheral tissues can be achieved. Consistent with this interpretation, using a conditional knockout strategy, Park et al (2010) recently found that 70% of mice with selective depletion of SMN in motor neurons survived over a year. Porensky et al (2012) reported that ICV injection of PMO ASO10-29 at a dose of 27, 54, or 81 mg in the SMND7 model (which has a slightly milder phenotype than the severe model that we used here) led to a sixfold to sevenfold survival increase; the investigators proposed that early and sustained increase of SMN in the CNS is essential for SMA therapy.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation